TRIBAL WOMEN PARTICIPATION IN AGRICULTURE AND ALLIED SECTORS IN GARIABAND DISTRICT OF CHHATTISGARH - Dhruw, Bebika; Kaushal, Reshma; Bhagat, Rohit; Attri, Narottam (International Journal of Research -GRANTHAALAYAH, 2020)
Agriculture is the most important and significant part of our life. It plays a vital role in Indian economy. Farm women’s are backbone of Indian agriculture. Present study was conducted at Teka and Kopra villages of Fingeshwar block, Gariaband district, Chhattisgarh. The aim of study is to ascertain the participation rate of tribal women of farm, wage discrimination, and constraints faced. A sample size of 150 households seventy-five each from two village viz. Teka and Kopra through random sampling method. The data was collected through structured interview schedule. Findings of the study that the per year participation of tribal households in different operations of farm were 250.07 man-days on an overall basis. Participation rate of tribal women in agriculture and allied sectors is high as compared to their male counterparts. The study revealed that the difference in wages of female and male wages was found to be much lower than the government wage rate. Major constraints of tribal women in the study area was low wages, less awareness on developmental programmes, lack of education, lack of freedom to take decision, health issues etc. there is need to put more attention on awareness programmes government schemes of scheduled tribes by the extension services.